1992
DOI: 10.1055/s-2006-961517
|View full text |Cite
|
Sign up to set email alerts
|

Identified Diallyl Polysulfides from an Aged Garlic Extract which Protects the Membranes from Lipid Peroxidation

Abstract: Garlic exerts various effects on the biological systems: e.g., inhibiting platelet aggregation (1-3), lowering serum and liver cholesterol levels (4, 5), and antibacterial activity (6). We have indicated that the aged garlic extract which was obtained by the ethanol-extraction of cracked garlic bulbs (Allium sativurn L.) protected biological membranes from lipid peroxidation (7). It is essential to clarify the component in garlic extract which has this antioxidant activity.We have tried to identify this compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(53 citation statements)
references
References 0 publications
1
50
0
2
Order By: Relevance
“…AGE treatment prevented the increase in MDA, probably in part by scavenging the very reactive hydroxyl and peroxyl radicals. Aged garlic extract and diallyl polysulfides inhibit the formation of thiobarbituric acid-reactive and fluorescent substances induced by iron-ascorbic acid in isolated liver microsomal membranes 17 , indicating the protective effect of garlic against lipid peroxidation. It has been reported that chronic garlic intake significantly decreased lipid peroxidation and increased endogenous antioxidants, such as catalase and GSH 5 .…”
Section: Discussionmentioning
confidence: 94%
“…AGE treatment prevented the increase in MDA, probably in part by scavenging the very reactive hydroxyl and peroxyl radicals. Aged garlic extract and diallyl polysulfides inhibit the formation of thiobarbituric acid-reactive and fluorescent substances induced by iron-ascorbic acid in isolated liver microsomal membranes 17 , indicating the protective effect of garlic against lipid peroxidation. It has been reported that chronic garlic intake significantly decreased lipid peroxidation and increased endogenous antioxidants, such as catalase and GSH 5 .…”
Section: Discussionmentioning
confidence: 94%
“…The members of the Allium family, including garlic, contain very high levels of biochemically active organic sulfur compounds, and their extracts have been known to protect organs from various injuries. [36][37][38] Since ROS have been implicated in mediating various pathological processes (e.g., ischemic heart disease, peripheral arterial occlusive disease, hypertension, hyperlipidemia, and toxicities), it can be suggested that the beneficial effects of garlic in these conditions may be due to its antioxidant activity. [39][40][41][42][43][44][45][46] The compounds in garlic (S-allylcysteine, S-allyl-mercapto cysteine, S-allyl-cysteine sulfoxide, and allicin), through their radical scavenging abilities, have been suggested to be responsible for its preventive effects against oxidative injury.…”
Section: Discussionmentioning
confidence: 99%
“…16,26,52 In the present study, AGE treatment significantly decreased MDA levels in the kidney, heart, and lung of CRF rats, probably in part, by scavenging the very reactive hydroxyl and peroxyl radicals. Horie et al 38 suggested that AGE and diallyl polysulfides inhibit the formation of TBA-reactive and fluorescent substances induced by iron-ascorbic acid in isolated liver microsomal membranes, indicating the protective effect of garlic against lipid peroxidation. Similarly, it was previously shown in several nephrotoxicity models that oxidative damage in the kidney tissue was prevented Garlic Extract Ameliorates Renal and Cardiopulmonary Injury 723 by AGE, which was demonstrated by reduced MDA levels and restored renal functions.…”
Section: Discussionmentioning
confidence: 99%
“…These components are recognized as antioxidant, antithrombotic, anticancer, antibacterial, antimicrobial, nematicidal, and insecticidal activity material (Al-Delaimy and Ali, 1970;Kamanna and Chandrasekhara, 1983;Horie et al, 1992;Kyung, 2006;Nuttakaan et al, 2006;Anwar et al, 2009). …”
Section: Open Access Research Articlementioning
confidence: 99%